Elaboramos dietas balanceadas tomando en cuenta las calorías - Cotrina Mejia, Juana (2018)
Rrelated to the personal elementaty school children development, this area contributes to the formation in their personality, intelligence and maturity, when it emphasizes the conscious implementation in their strategies and learning possibilities and marveling at the surrounding phenomena. In the Area contents, special attention is given to issues related to health preservation. Good nutrition and a balanced diet help children grow up healthy. It doesn't matter if your child is a young child or a teenager, you can take steps to improve their nutrition and form good eating habits. The top five strategies are: Establish a regular family meal time, serve healthy foods variaty and snacks, set a good example by following a nutritious diet, avoid fighting over food, Involve children in the process. However, it is not easy to take these measures. Our days are full of responsibilities, and fast food is always at hand. Children, especially the youngest ones, eat mostly what is available in the house. That's why it's important to keep an eye on your supplies: the foods you serve at meals and the foods you keep at hand for snacks. The best way to encourage your child to eat healthy is by the example. Children imitate the adults if they see every day. you eat fruits and vegetables, and eat less non nutritious foods, you are sending the right message.